Aortic Sources of Embolism - Viedma-Guiard, Elena; Guidoux, Celine; Amarenco, Pierre; Meseguer, Elena (Frontiers in Neurology, 2021)
Aortic arch atheroma is a frequent finding in ischemic stroke patients. Its role as a source of cerebral emboli or a marker of atherosclerosis is unclear. Transesophageal echography is considered the gold standard for its detection, whereas computed tomography angiography is a good alternative; magnetic resonance and positron emission tomography could be proposed to better analyze plaque vulnerability. Despite the interest in this condition, the optimal antithrombotic treatment remains uncertain, while intensive lipid-lowering therapy should be recommended. This review aims to offer guidance on patients with aortic arch atheroma, about its causal role in stroke, diagnosis, and treatment based on current available evidence.